2018
DOI: 10.1016/j.jaci.2017.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Sputum autoantibodies in patients with severe eosinophilic asthma

Abstract: This study identifies an autoimmune endotype of severe asthma that can be identified by the presence of sputum autoantibodies against EPX and autologous cellular components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 40 publications
9
128
1
1
Order By: Relevance
“…When the detection antibody was switched to a biotinylated secondary antibody (AP-ELISA), the OD values generated for the EPX-spiked diluent control was considerably lowered (0.092). Similar observations were seen during protocol optimisation of an anti-EPX IgG ELISA (Mukherjee et al, 2017). The mean OD value (± standard deviation) generated for the same set of samples (paucigranulocytic vs. eosinophilic sputa) with an HRP-labelled secondary antibody (Abcam) was 1.7±0.9 vs. 2.2±0.4 (n = 4, p = 0.1, paired t-test).…”
Section: Resultssupporting
confidence: 79%
“…When the detection antibody was switched to a biotinylated secondary antibody (AP-ELISA), the OD values generated for the EPX-spiked diluent control was considerably lowered (0.092). Similar observations were seen during protocol optimisation of an anti-EPX IgG ELISA (Mukherjee et al, 2017). The mean OD value (± standard deviation) generated for the same set of samples (paucigranulocytic vs. eosinophilic sputa) with an HRP-labelled secondary antibody (Abcam) was 1.7±0.9 vs. 2.2±0.4 (n = 4, p = 0.1, paired t-test).…”
Section: Resultssupporting
confidence: 79%
“…Furthermore, Bland-Altman analysis shows the sLFT has a bias toward underestimating EPX when compared to the ELISA (Figure 1F, mean −6.44; 95% CI -24.79 to 11.90). 9 Indeed, samples that reported lower values of EPX on the LFT compared to the standard ELISA values, recorded higher titers of anti-EPX IgG, suggesting that the presence of endogenous anti-EPX antibodies could be a confounding factor in EPX capture on LFTs (Figure 1E). 9 Therefore, we sought to examine (i) whether the presence of endogenous autoantibodies to EPX was responsible for reducing EPX detection on the LFTs in eosinophilic samples and (ii) whether removal by an immunoprecipitation (IP) technique would improve detection on the LFTs (the strategy for which has been outlined in Figure 2A).…”
Section: Rapid Quantification Of Sputum Eosinophil Peroxidase On a Lamentioning
confidence: 94%
“…To our surprise, we observed a significant decrease in quantifiable EPX using this technique when compared to the gold standard ELISA ( Figure 1E, P = .004). 9 Therefore, we sought to examine (i) whether the presence of endogenous autoantibodies to EPX was responsible for reducing EPX detection on the LFTs in eosinophilic samples and (ii) whether removal by an immunoprecipitation (IP) technique would improve detection on the LFTs (the strategy for which has been outlined in Figure 2A). Recent work from our group has shown that a third of asthmatics with eosinophilic inflammation have demonstrable titers of anti-EPX IgGs in their sputum, correlating significantly with markers of degranulation.…”
Section: Rapid Quantification Of Sputum Eosinophil Peroxidase On a Lamentioning
confidence: 99%
“…Taken together, these studies demonstrate the strength of translational research in using a wide range of methods to move from the identification of novel treatment targets to clinical use over a relatively short time span. Examples of how translational research has evolved our understanding of OAD and has resulted in novel treatments are illustrated in Figure …”
Section: The Role Of Translational Research In Evolving Management Ofmentioning
confidence: 99%
“…There is accumulating evidence to suggest that clinically, airway sampling will be necessary in order to obtain a complete immunological status and guide treatment decisions in OAD: some patients only have eosinophilic inflammation in their airways and not systemically, and neutrophilic airway inflammation can only be assessed in airway samples . Eosinophilic airway inflammation in patients with steroid‐refractory asthma may be driven by airway autoimmunity . Patients who do not respond to an anti‐IL‐5 may have eosinophilic airway inflammation despite normalization of blood eosinophils .…”
Section: Clinical Adaptation Of Novel Treatments For Oad: Barriers Anmentioning
confidence: 99%